2021
DOI: 10.1109/access.2021.3107467
|View full text |Cite
|
Sign up to set email alerts
|

RTEAM: Risk-Based Trust Evaluation Advanced Model for VANETs

Abstract: In Vehicular ad hoc networks (VANETs), vehicles share and exchange information regarding road safety and traffic conditions. Thus, trust is established among vehicles to ensure the integrality and reliability of the received reports. Ensuring the security of VANETs is the key to enhance road safety, and for this purpose, several trust establishing, evaluation, and management models have been proposed. When a vehicle receives conflicting reports about an event such as a car accident from its neighboring vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…A holistic overview of the existing trust management mechanisms reveals that a number of trust-based parameters have been applied in different settings in order to measure and evaluate trust. The trust-based parameters include, but are not limited to, resource availability [6], similarity [19,25,26], familiarity [6,7,22,27], timeliness [7], context [19,20,28,29], cooperativeness [19,30], community-of-interest (CoI) [19,30], confidence [31,32], reward [28,33], attitude, subjective norms, and perceptual behavioral control [5], freshness of data [34], and packet delivery ratio [7,25,31,35,36]. Also, the selection of a trust-based threshold for determining trustworthy and untrustworthy behavior is crucial.…”
Section: Trust Parameters and Evaluation Parametersmentioning
confidence: 99%
“…A holistic overview of the existing trust management mechanisms reveals that a number of trust-based parameters have been applied in different settings in order to measure and evaluate trust. The trust-based parameters include, but are not limited to, resource availability [6], similarity [19,25,26], familiarity [6,7,22,27], timeliness [7], context [19,20,28,29], cooperativeness [19,30], community-of-interest (CoI) [19,30], confidence [31,32], reward [28,33], attitude, subjective norms, and perceptual behavioral control [5], freshness of data [34], and packet delivery ratio [7,25,31,35,36]. Also, the selection of a trust-based threshold for determining trustworthy and untrustworthy behavior is crucial.…”
Section: Trust Parameters and Evaluation Parametersmentioning
confidence: 99%
“…To improve the effectiveness of communication in VANETs in earlier research several trust models are introduced in VANETs. They are trust cascading-based emergency message dissemination (TCEMD) model [13], risk-based trust evaluation advanced model (RTEAM) [14], trust model for location privacy protection [15], context-aware trust management model [16], anonymous cloaking zone creation approach based on a trust mechanism [17], "VAR2" strategy that permits autonomous trust model [18], a vehicle trust evaluation approach based on a hidden markov model (HMM) that increases the accuracy in the identification of malicious activity [19], a trusted routing strategy based on block-chain and fuzzy logic to enhance the identification of rogue nodes in VANET [20], a consortium block-chain-based strategy for preventing insider assaults in the VANET system utilizing the trusted AODV protocol [21], adaptive traffic-management system (ATM), an effective active-detection trust management system [22], the trust model to protect the UAVs assisted VANETs [23], UAV-assisted ubiquitous trust evaluation (UUTE) framework [24], and lightweight attestation mechanism [25]. Once after analysis the earlier research which is based on trust in UAV assisted VANETs the major drawback which is identified are increased energy consumption, delay and overhead in the network.…”
Section: Related Workmentioning
confidence: 99%
“…The author concluded by testing and developing various vehicle safety technologies. It also combines a security risk assessment framework established by taking the GMITS model as an example to assess threats and vulnerabilities [9]. This research was focused on the AI stock, this one provides a solution called Stock-AssIstant that models the reliability of stock commentary by taking into account a variety of factors such as stock price movements, commentary content, and analyst performance.…”
Section: Related Researchmentioning
confidence: 99%